Subgroup Analysis Stratified by Baseline Pancreatic β-cell Function in a Japanese Study of Dulaglutide in Patients with Type 2 Diabetes - Iwamoto, Noriyuki (Diabetes Ther, 2017)
INTRODUCTION: This analysis investigated the relationship between baseline fasting pancreatic β-cell function and efficacy in Japanese patients with type 2 diabetes (T2D) treated with once-weekly dulaglutide 0.75 mg (dulaglutide) or once-daily liraglutide 0.9 mg (liraglutide) for up to 52 weeks. METHODS: In a 52-week study of monotherapy in Japanese patients with T2D, patients were categorized into three subgroups defined by tertiles (low, medium, and high) of baseline values of three pancreatic β-cell function parameters [fasting C-peptide, C-peptide index, and secretory units of islets in transplantation (SUIT) index]. Associations between these parameters and efficacy [defined by changes from baseline in glycated hemoglobin (HbA1c), fasting blood glucose (FBG), postprandial blood glucose (PBG), mean of all meals blood glucose excursion, and body weight] in the dulaglutide group (280 patients) or the liraglutide group (137 patients) were evaluated. RESULTS: Patients in the subgroups with high insulin-secreting ability (based on pancreatic β-cell function) were younger and had shorter disease duration and higher body mass index compared to those with low insulin-secreting ability. No specific trend was observed between baseline pancreatic β-cell function and changes in HbA1c or FBG. Reductions from baseline in mean PBG and excursion were greatest for patients in the low β-cell function tertiles. Inconsistent trends in body weight were observed across the treatment groups and β-cell function parameters. CONCLUSION: In Japanese patients with T2D, changes in HbA1c and body weight after 52 weeks of treatment with dulaglutide or liraglutide could not be predicted by patients’ fasting pancreatic β-cell function before treatment. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov (NCT01558271). FUNDING: Eli Lilly K.K. (Kobe, Japan).